Epidemiology of Spontaneous Abortions: The Effects of Alcohol Consumption and Cigarette Smoking - Anokute, Charles C. (1986)
A prospective epidemiologic study of spontaneous abortions and fetal wastage was undertaken over a period of 12 months in Oklahoma City. A total of 1,050 pregnant women were followed from their first prenatal visit until the termination of pregnancy. In addition to the available information in the patients' medical records, a questionnaire was administered to each patient during her first visit. Detailed information was sought on the patient's smoking and drinking habits. Alcohol and cigarettes were found to have an independent, positive association with adverse pregnancy outcome. A dose-response relationship was observed, and a synergistic effect was illustrated.